Identification and Verification of Potential Hub Genes in Amphetamine-Type Stimulant (ATS) and Opioid Dependence by Bioinformatic Analysis - Zhang, Wei; Deng, Xiaodong; Liu, Huan; Ke, Jianlin; Xiang, Mingliang; Ma, Ying; Zhang, Lixia; Yang, Ming; Liu, Yun; Huang, Feijun (Frontiers in Genetics, 2022)
Objective: Amphetamine-type stimulants (ATS)- and opioid- dependence were chronic inflammatory diseases with similar symptoms and common genomics. However, their co-expressive genes had not been thoroughly investigated. We aimed to identify and verify co-expressive hub genes and pathway involved in the pathogenesis of ATS- and opioid- dependence. Methods: The microarray of ATS- and opioid- treatment mouse model obtained from the GEO databases, respectively. GEO2R and Venn diagram were performed to identify differentially expressed genes (DEGs) and co-expressive DEGs (CDEGs). Functional annotation and PPI network detected the potential functions. The hub genes were screened using CytoHubba and MCODE plugin with different algorithms, and further validated by ROC analysis in GSE15774 database. We also validated the hub genes mRNA levels in BV2 cells using qPCR. Result: Forty-four CDEGs were identified between ATS- and opioid- databases, which were prominently enriched in PI3K/AKT signaling pathway. The top 10 hub genes mainly enriched in apoptotic process (CD44, Dusp1, Sgk1, Hspa1b), neuron differentiation, migration, and proliferation (Nr4a2, Ddit4), response to external stimulation (Fos, Cdkn1a), and transcriptional regulation (Nr4a2, Npas4). Receiver operating characteristic (ROC) analysis found that six hub genes (Fos, Dusp1, Sgk1, Ddit4, Cdkn1a, and Nr4a2) with Area Under the Curve (AUC) more than 0.70 in GSE15774. The mRNA levels of Fos, Dusp1, Sgk1, Ddit4, Cdkn1a, PI3K, and AKT in BV2 cells and GSE15774 with METH- and heroin- treatment was higher than those of controls. However, the Nr4a2 mRNA levels increased in BV2 cells, and decreased in bioinformatic analysis. Conclusions: The identification of hub genes was associated with ATS- and opioid- dependence, which involved in apoptosis, neuron differentiation, migration and proliferation. PI3K/AKT signaling pathway might play a critical role in the pathogenesis of substance dependence.